أثر المقاربة النصية في تنمية المهارات اللغوية للسنة الرابعة متوسط - زكرود, منصورية (كلية الأدب العربي والفنون, 2024)
تناولت الدراسة موضوعا مهما في حقل التربية و التعليم في ظل التطورات الحاصلة في المنظومة التربوية في مرحلة التعليم المتوسط ألا وهي ،" أثر المقاربة النصية في تنمية المهارات اللغوية للسنة الرابعة متوسط ". قسمت دراستي إلى مدخل و فصلين و خاتمة حيث تطرقت في المدخل إلى أنواع المقاربات التعليمية بدءا بالمضامين مرورا بالأهداف وصولا إلى الكفاءات. وقد تناولت في الفصل الأوّل كل ما يتعلق بالمقاربة النصية انطلاقا بماهيتها و أبعادها وصولا إلى المهارات اللغوية ، وتعلمها في ضوء المقاربة النصية ، من استماع ، و قراءة و كتابة ، و تحدث . أمّا الفصل الثاني فكان تطبيقي جاء فيه تحليل برنامج دروس السنة الرابعة متوسط ليخلص في النهاية بعرض نموذجي لطريقة التدريس بهذه المقاربة بالاعتماد على تحليل مذكرات الأساتذة . و في الأخير أنهيت عملي بخاتمة تضمنت أهم النتائج التي توصلت إليها من خلال هذه الدّراسة . The study addressed an important topic in the field of education in light of the developments taking place in the educational system in the intermediate education stage ,namely “ the effect of the textual approach in developing language skills for the fourth year of intermediate school” .I divided my study into in introduction ,two chapters ,and a conclusion .In the introduction ,I discussed the types of educational approaches the types educational approaches ,starting through the objectives, and reaching the competencies. In the first chapter ,I dealt with everything related to the textual approach , starting with its nature and dimensions , all the way to linguistic skills and learning them in light of the textual approach ,such as listening , reading ;writing , and he spoke. As for the second chapter ,it was my application , with included an analysis of the program of lessons for the fourth intermediate year, concluding at the end with an exemplary presentation of the teaching method with this approach , based on the analysis of the teachers’notes .Finally, I concluded my work a conclusion that included the most important results that were reached through this study
Keywords: المقاربة ، النص ، المقاربة النصية ، المهارات اللغوية; approach , text , textual approach , linguistic skills